Neural Responses to Reward and Punishment Stimuli in Depressed Status Individuals and Their Effects on Cognitive Activities - Li, Yutong; Cheng, Xizi; Li, Yahong; Sui, Xue (Frontiers in Psychology, 2022)
Depressed individuals respond abnormally to reward stimuli, but the neural processes involved remain unclear. Whether this neural response affects subsequent cognitive processing activities remains to be explored. In current study, participants' choice behaviors were rewarded and punished, and their neural responses were recorded. The subjects were then asked to complete cognitive processing tasks. The results showed that the accuracy rate of the two groups was significantly higher after loss feedback than after gain feedback. The time to complete cognitive tasks was longer in the depressed group than in the healthy group. Analysis of EEG data showed that the amplitude of RewP induced by gain feedback was larger than that induced by loss feedback, and the amplitude of RewP and fb-P3 induced by depression group was smaller than that of healthy group. The study also found that the amplitude of RewP and fb-P3 induced by the gain feedback was positively correlated with the subsequent cognitive processing accuracy of the healthy group, but no such association was found in the depression group. The results showed that the neural response of depressed individuals to reward and punishment stimuli was weakened and the subsequent cognitive processing was affected. This study supports the emotion context insensitivity hypothesis.